Konsistensi Penerapan Ketentuan Ambang Batas dalam Putusan MK pada Sengketa Pilkada: (Studi Kasus Putusan 55/PHPU.BUP-XXIII/2025 Gorontalo Utara 2024) - Siska Ahaya; Nurwita Ismail; Arifin Tumuhulawa (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Settlement of disputes over regional head election results is a crucial instrument to ensure democracy, legal certainty, and electoral justice. In practice, the Constitutional Court does not always apply the vote margin threshold rigidly, particularly when violations are identified that may affect the integrity of the electoral process. This study aims to analyze the consistency of Constitutional Court decisions in resolving disputes over regional head election results, focusing on the application of the vote margin threshold, using Constitutional Court Decision No. 55/PHPU-BUP-XXIII/2025 as a case study. It also examines the effectiveness of the decision in resolving the North Gorontalo Regency election dispute and its implications for legal certainty and regional government stability. This research employs normative legal methods with statutory and conceptual approaches. Primary legal materials include legislation and Constitutional Court decisions, while secondary materials consist of books, journals, and relevant prior studies. The analysis is conducted qualitatively using theories of legal certainty, legal effectiveness, and legal compliance. The findings show that Decision No. 55/PHPU-BUP-XXIII/2025 reflects inconsistency in applying Article 158 of Law No. 10 of 2016, as the Court waived the vote margin threshold despite the alleged violation not directly affecting the election outcome. However, this approach was justified to uphold substantive justice and safeguard democratic integrity. Therefore, clearer and more consistent parameters are needed regarding the conditions under which Article 158 may be waived to ensure both legal certainty and substantive justice in future electoral dispute resolution.